2020
DOI: 10.4102/jef.v13i1.461
|View full text |Cite
|
Sign up to set email alerts
|

Tax knowledge for the digital economy

Abstract: Orientation: Because of the digital economy, taxpayers have access to new income streams. These virtual transactions have taxation consequences, and therefore taxpayers need specialised taxation knowledge to understand their tax obligations and act in a tax compliant manner.Research purpose: The aim of this article was to identify the unique tax knowledge requirements for individuals functioning in the digital economy by systematically reviewing literature on the tax challenges arising from this new economy. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
26

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 29 publications
1
18
0
26
Order By: Relevance
“…Similar results were received by Lewis (1982) explains that tax knowledge correlates negatively with tax compliance behaviour. However, these results contradict many other research outcomes in those researchers found that positive correlation exists between tax knowledge and tax compliance behavior (Harris, 1989;Singh, 2003;Singh and Bhupalan, 2001;Mohamad Ali et al 2007;Wassermann & Marina, 2020). Malaysian thinking that it takes hard work to meet the basic needs and looking closely to find ways to control costs since tax knowledge has a negative association with tax compliance behavior in Malaysia.…”
Section: Income Levelmentioning
confidence: 79%
See 1 more Smart Citation
“…Similar results were received by Lewis (1982) explains that tax knowledge correlates negatively with tax compliance behaviour. However, these results contradict many other research outcomes in those researchers found that positive correlation exists between tax knowledge and tax compliance behavior (Harris, 1989;Singh, 2003;Singh and Bhupalan, 2001;Mohamad Ali et al 2007;Wassermann & Marina, 2020). Malaysian thinking that it takes hard work to meet the basic needs and looking closely to find ways to control costs since tax knowledge has a negative association with tax compliance behavior in Malaysia.…”
Section: Income Levelmentioning
confidence: 79%
“…When considering the attitudes of individual taxpayers, the tax law knowledge is essential. (Manual & Xin, 2016;Wassermann & Marina, 2020) and tax knowledge forms a significant positive association with tax compliance level (Mukhlis et al, 2015). Despite the fact that limited research focusing on tax knowledge, it has been found that education do shows a vital role since the application of the Self-Assessment System that required personal tax knowledge (Kasipillai et al, 2003;Harijito, 2005).…”
Section: Tax Knowledgementioning
confidence: 99%
“…Literasi pajak berkorelasi positif dengan kepatuhan pajak (Bornman and Wassermann, 2019). Oleh karena itu, literasi pajak perlu ditingkatkan untuk meningkatkan kepatuhan Wajib Pajak (Susyanti dan Anwar, 2020) .…”
Section: Pendahuluanunclassified
“…Knowing that something is taxable merupakan pemahaman WP tentang ketentuan hukum dan Undang-Undang Perpajakan dan mengetahui bahwa ada sesuatu yang dikenakan pajak (Bornman and Wassermann, 2019). Dengan memahami dan mengetahui cara menerapkan ketentuan hukum perpajakan yang berlaku (Bornman dan Wassermann, 2019) akan terdapat kecenderungan bagi WP untuk memeriksa kembali penghitungan pajak terutangnya sehingga semakin tinggi tingkat literasinya.…”
Section: Legal Knowledgeunclassified
See 1 more Smart Citation